Synthesis, characterization and biological activity of NitrogenOxygen-Sulfur (NOS) transition metal complexes derived from novel s-2,4-dichlorobenzyldithiocarbazate with 5-fluoroisatin / Mohd Abdul Fatah Abdul Manan ... [et al.] - Abdul Manan, Mohd Abdul Fatah; Bahron, Hadariah; Kassim, Karimah; Muhamad, Mohd Asrul Hafiz; Sayed Mohamad, Syed Nazmi (Research Management Institute (RMI), 2010)
A novel Schiff base containing nitrogen-oxygen-sulfur (NOS) donor atoms formed from the condensation reaction of S-2,4dichlorobenzyldithiocarbazate (S-2.4BDTC) with 5-fluroisatin has been synthesized. Complexes of cobalt(ll), nickel(ll), copper(ll), zinc(ll) and cadmium(ll) with this Schiff base have been prepared and characterized using elemental analysis and various physico-chemical techniques. In the cobalt(ll) andnickel(II) complexes the SchifJbase behaves as a uninegatively charged tridentate nitrogen-oxygen-sulfur (NOS) chelating ligand, bonding through the azomethine nitrogen, thiolate sulfur and carbonylic oxygen of the isatin moiety. However. in the copper(ll), zinc(II) and cadmium(II) complexes the Schiff base behaves as a nitrogen-sulfur (NS) bidentate chelating ligand, bonding through the azomethine nitrogen and thiolate sulfur. The Schiff base and the metal complexes were evaluated with respect to antimicrobial activity, which was performed in reallion to two selected pathogenic microbials (Bacillus subtilis and Pseudomonas aeruginosa). It was observed that only the zinc Schiffbase complex exhibited strong activity against the Bacillus subtilis bacteria with an inhibition zone of 25 mm.